Modulation of Colorectal Cancer Risk by Polymorphisms in 51Gln/His, 64Ile/Val, and 148Asp/Glu of APEX Gene; 23Gly/Ala of XPA Gene; and 689Ser/Arg of ERCC4 Gene - L. Dziki; A. Dziki; M. Mik; I. Majsterek; J. Kabzinski (Gastroenterology Research and Practice)
Polymorphisms in DNA repair genes may affect the activity of the BER (base excision repair) and NER (nucleotide excision repair) systems. Using DNA isolated from blood taken from patients (n=312) and a control group (n=320) with CRC, we have analyzed the polymorphisms of selected DNA repair genes and we have demonstrated that genotypes 51Gln/His and 148Asp/Glu of APEX gene and 23Gly/Ala of XPA gene may increase the risk of colorectal cancer. At the same time analyzing the gene-gene interactions, we suggest the thesis that the main factor to be considered when analyzing the impact of polymorphisms on the risk of malignant transformation should be intergenic interactions. Moreover, we are suggesting that some polymorphisms may have impact not only on the malignant transformation but also on the stage of the tumor.